Lack of beta-arrestin signaling in the absence of active G proteins - Manuel Grundmann (Nature Portfolio, 2018)
Arrestins terminate signaling from GPCRs, but several lines of evidence suggest that they are also able to transduce signals independently of G proteins. Here, the authors systematically ablate G proteins in cell lines, and show that arrestins are unable to act as genuine signal initiators.